A Pavilion in the Danish forest by Vilhelm Wohlert; Tradition and Modernity - García Sánchez, Carmen (Ge-conservacion, 2017)
Danish architect Vilhelm Wohlert (1920-2007), after a stay as a guest teacher at Berkeley University, designs his first building. Created in a period of a flourishing architecture, it achieves a balance between Danish tradition and modernity, where international references -American architecture and Japanese tradition- are significant. Its ability to fit into the circumstances, sets a model for the buildings of the future. There is a dialogue with the surrounding nature, her careful observation; establishing a great connection, where the Danish attitude towards her is not a domination. The architect knows the material and uses it in harmony with its essence. The study suggests that the vernacular may be a process that evolves and transforms over time involving a significant level of modernity, and that a look at it could be an answer to prevent the loss the identity of architecture.